Impact of an SLC30A8 loss-of-function variant on the pancreatic distribution of zinc and manganese: laser ablation-ICP-MS and positron emission tomography studies in mice - Firth, George; Georgiadou, Eleni; Griffiths, Alexander; Amrahli, Maral; Kim, Jana; Yu, Zilin; Hu, Ming; Stewart, Theodora J.; Leclerc, Isabelle; Okamoto, Haruka; Gomez, Daniel; Blower, Philip J.; et al. (Frontiers in Endocrinology, 2023)
Common variants in the SLC30A8 gene, encoding the secretory granule zinc transporter ZnT8 (expressed largely in pancreatic islet alpha and beta cells), are associated with altered risk of type 2 diabetes. Unexpectedly, rare loss-of-function (LoF) variants in the gene, described in heterozygous individuals only, are protective against the disease, even though knockout of the homologous SLC30A8 gene in mice leads to unchanged or impaired glucose tolerance. Here, we aimed to determine how one or two copies of the mutant R138X allele in the mouse SLC30A8 gene impacts the homeostasis of zinc at a whole-body (using non-invasive 62Zn PET imaging to assess the acute dynamics of zinc handling) and tissue/cell level (using LA-ICP-MS to map the long-term distribution of zinc and manganese in the pancreas). Following intravenous administration of [62Zn]Zn-citrate (~7 MBq, 150 μL) in wild-type (WT), heterozygous (R138X+/-) and homozygous (R138X+/+) mutant mice (14-15 weeks old, n = 4 per genotype), zinc dynamics were measured over 60 minutes using PET. Histological, islet hormone immunohistochemistry and elemental analysis with LA-ICP-MS (Zn, Mn, P) were performed on sequential pancreas sections. Bulk Zn and Mn concentration in the pancreas was determined by solution ICP-MS. Our findings reveal that whereas uptake into organs, assessed using PET imaging of 62Zn, is largely unaffected by the R138X variant, mice homozygous of the mutant allele show a substantial lowering (to 40% of WT) of total islet zinc, as anticipated. In contrast, mice heterozygous for this allele, thus mimicking human carriers of LoF alleles, show markedly increased endocrine and exocrine zinc content (1.6-fold increase for both compared to WT), as measured by LA-ICP-MS. Both endocrine and exocrine manganese content were also sharply increased in R138X+/- mice, with smaller increases observed in R138X+/+ mice. These data challenge the view that zinc depletion from the beta cell is the likely underlying driver for protection from type 2 diabetes development in carriers of LoF alleles. Instead, they suggest that heterozygous LoF may paradoxically increase pancreatic β-cell zinc and manganese content, and also impact the levels of these metals in the exocrine pancreas, to improve insulin secretion.